Substitution site and effects on magnetism in Sr-for-Ca substituted CaBaCo4O7 - Aurelio, Gabriela (2015)
Cationic substitutions in the novel magnetoelectric compound CaBaCo4O7 lead to profound changes in its magnetic and electric behaviors. In this work, we present a structural study of the isovalent substitution Sr-for-Ca in CaBaCo4O7. X-ray diffraction, as well as neutron powder diffraction experiments, are reported for a series of samples Ca1-xSrxBaCo4O7 with 0 ≤ x ≤ 0.10. Special emphasis is given to the identification of the substitution site, as Sr has also been reported to substitute for Ba in this crystal structure. The solubility limit for Sr at the Ca site is shown to be at x ≃ 0.08. The variation of lattice constants with Sr-doping firmly supports the Sr-for-Ca substitution. Rietveld refinements of the Sr-substituted samples are presented, and used as starting point to analyse the local structure around Sr by means of X-ray absorption spectroscopy at the Sr K-edge. Both the near-edge absorption and the extended absorption fine-structure confirm the substitution of Sr for Ca, giving definite support to the proposed nominal formula. In addition, macroscopic magnetization measurements are presented which reveal the striking effects of Sr-substitution over the magnetic landscape of this puzzling compound.